Status Hukum Harta Perkawinan Jika Terjadi Kepailitan Suami/Istri Tanpa Adanya Perjanjian Kawin - Putu Indri Sri Giyanthi; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
Marriage is carried out by a male and female couple to continue their offspring. In marriage, if the husband and wife do not make a marriage agreement, it will have an impact on the marital property, especially if one of the parties is declared bankrupt. This study reviews the legal arrangements for marital property in Indonesia and reveal the legal consequences of marital property in the event of husband/wife bankruptcy without a marriage agreement. This research uses a normative method with a Legislative approach. Law is the object of research. The legal sources used are primary and secondary legal data. Furthermore, the research results are described qualitatively. The results showed that the legal regulation of marital property is regulated in Article 35 of the Marriage Law Number 1 of 1974 Jo. Law Number 16 of 2019 which regulates joint assets and inherited assets, and also in Article 119 of the Civil Code which regulates the unity of assets. The legal consequences of marital property if one of the parties goes bankrupt in the event that the marriage requires a union of assets will result in joint bankruptcy of husband and wife in accordance with the provisions of Article 64 paragraph (1) of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations.